DOI: 10.22215/etd/2007-07584
|View full text |Cite
|
Sign up to set email alerts
|

The effects of instructor immediacy behaviours on student learning experience in an online course

Abstract: The author has granted a non exclusive license allowing Library and Archives Canada to reproduce, publish, archive, preserve, conserve, communicate to the public by telecommunication or on the Internet, loan, distribute and sell theses worldwide, for commercial or non commercial purposes, in microform, paper, electronic and/or any other formats. AVIS: L'auteur a accorde une licence non exclusive permettant a la Bibliotheque et Archives Canada de reproduire, publier, archiver, sauvegarder, conserver, transmettr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 29 publications
(171 reference statements)
0
1
0
Order By: Relevance
“…These studies have suggested that high immediacy communication signals familiarity in public communication on social media (Bazarova et al, 2012), closeness in relationships (Pennebaker & King, 1999), and informality of the setting (Biber, 1988; Pennebaker & King, 1999). The use of language with high immediacy has also been associated with a number of positive social outcomes, including compliance and persuasion (Mehrabian, 1968; Riggio et al, 1989), student participation and affective and cognitive learning in education (Gorham, 1988; Allen et al, 2006; Khan, 2007), effective problem solving and satisfaction among married couples (Simmons et al, 2005), and satisfaction and team cohesion in sports teams (Turman, 2008). …”
mentioning
confidence: 99%
“…These studies have suggested that high immediacy communication signals familiarity in public communication on social media (Bazarova et al, 2012), closeness in relationships (Pennebaker & King, 1999), and informality of the setting (Biber, 1988; Pennebaker & King, 1999). The use of language with high immediacy has also been associated with a number of positive social outcomes, including compliance and persuasion (Mehrabian, 1968; Riggio et al, 1989), student participation and affective and cognitive learning in education (Gorham, 1988; Allen et al, 2006; Khan, 2007), effective problem solving and satisfaction among married couples (Simmons et al, 2005), and satisfaction and team cohesion in sports teams (Turman, 2008). …”
mentioning
confidence: 99%